Monitoring Occupational Shortages : Lessons from Malaysia's Critical Occupations List - World Bank Group (World Bank, Malaysia, 2019)
Many emerging economies have skills shortages but fail to effectively deploy students andjob seekers towards filling those shortages. In emerging economies, new technologies,digitization, automation, and other trends like Industry 4.0 result in a constantly changing demandfor sophisticated skills. In this environment, there are often students and job seekers who couldpotentially fill skills gaps but face significant challenges in identifying job opportunities andthe skills needed to obtain them. The schools, training centers, and public service providers thatare responsible for preparing the workforce to fill skills gaps often face similar challenges in terms of deploying attention and resources towards filling those gaps. In Malaysia, the Critical Skills Monitoring Committee (CSC) is charged with producing a Critical Occupations List to serve as a platform for coordinating human capital development policies. The CSC is a specialized interagency body that was established as part of the Eleventh Malaysia Plan to monitor skills imbalances in Malaysia. To do so, the CSC created an annual Critical Occupations List (COL) of occupations that are middle- or highskilled, sought-after, and strategic. The COL has evolved during the last several years to become a best-practice tool for monitoring skills. The COL is updated regularly and improved continually, is based on rigorous evidence, and is widely circulated. The production of the list is undertaken by the CSC and incorporates a wide range of input from both the public and private sector.